The media’s coverage of mass public shootings in America: fifty years of newsworthiness - Silva, Jason R. (International journal of comparative and applied criminal justice, 2019)
This study uses a media distortion analysis to examine the New York Times coverage of mass public shooting incidents occurring in the United States from 1966 to 2016. A comparison between media coverage and actual incidents is used to identify the characteristics influencing the newsworthiness of mass public shootings. This work expands the breadth and depth of media and mass public shooting research, strengthening the validity of previous findings, and identifying new characteristics influencing newsworthiness. Findings indicate significant predictors of newsworthiness include higher casualties and injuries, as well as perpetrators that are young, Middle Eastern, and ideologically motivated. School shootings are more likely to receive any coverage, and all non-workplace shootings receive salient levels of coverage. An incident is also more likely to receive any coverage if a combination of weapons is used. These findings have important implications for public knowledge and perceptions of mass public shootings.